Preoperative Alpha-Fetoprotein Has No Prognostic Role in Small Hepatocellular Carcinoma in Non-Cirrhotic Patients After Surgical Resection - Gao, Tian-Ming; Bai, Dou-Sheng; Qian, Jian-Jun; Chen, Ping; Jin, Sheng-Jie; Jiang, Guo-Qing (Turkish Journal of Gastroenterology, 2021)
Background/Aims: Alpha-fetoprotein (AFP) has been widely used as a tumor marker in the treatment of hepatocellular carcinoma (HCC) in patients with cirrhosis. However, a large portion of HCC patients are diagnosed without cirrhosis, and the prognostic capability of AFP was unclear in HCC patients without cirrhosis. Our purpose was to investigate the prognostic efficiency of AFP in patients with non-cirrhosis, single, and small HCC who were treated with surgical resection.Materials and Methods: Among the 111,374 liver cancer patients included in the SEER database, we selected 224 patients without cirrhosis with a single HCC ≤ 3 cm in diameter identified at diagnosis who were treated with surgical resection. The AFP test results were recorded as AFP-positive and AFP-negative levels. Results: Kaplan-Meier method showed that there was not significantly survival different between AFP-positive and AFP-negative groups (P = 0.566). The same results were found in the subgroups of patients with tumor size ≤ 2 cm and 2–3 cm (P = 0.710 and 0.687, respectively). ROC curve analysis showed that AFP had inadequate accuracy to discriminate survivors and deceased patients in subgroups of patients with tumor size ≤ 3 cm, 2–3 cm or ≤ 2 cm (area under the ROC curve = 0.449, 0.458, 0.443; 95% confidence interval = 0.366–0.533, 0.346–0.571, 0.317–0.569, respectively). Conclusion: AFP levels has no predictive value in well-compensated non-cirrhosis patients with single, small HCC (≤ 3 cm) treated with surgical resection for curative intent.